The English teachers' perceptions of discovery learning and project-based learning at senior high school in Lombok West Nusa Tenggara - Amrullah Amrullah; Sahuddin Sahuddin; Nawawi Nawawi; Lalu Nurtaat (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
This study explores the perceptions of English teachers in Lombok, West Nusa Tenggara, Indonesia, regarding Discovery Learning (DL) and Project-Based Learning (PjBL) in senior high school settings. The research employed a descriptive qualitative approach, involving questionnaire sheet, interviews, and document analysis to gather data from two English teachers at SMKN 1 Kuripan and three English teachers at MAN 1 Lombok Timur who use or have used the DL and PjBL models. The findings indicated that teachers' perceptions on both teaching models are highlighting their effectiveness in engaging students actively, fostering critical thinking and problem-solving skills, and promoting student-centered learning environments. In addition to their effectiveness, the implementation of these models also have challenges there are often faced by the teachers, including addressing varying levels of student prior knowledge, managing time constraints, and resourcing limitations. Despite these challenges, the teachers have adopted the way to overcome them, such as adapting their approach to accommodate students’ diverse needs, seeking professional development opportunities, and employing collaborative strategies. The study concludes that understanding teachers’ perceptions and addressing the challenges associated with implementing innovative teaching models is crucial for optimizing student learning outcomes in English language instruction.